Lord of the flies - Brook, Peter; Aubrey, James; Chapin, Tom; Edwards, Hugh, 1951-; Elwin, Roger; Gaman, Tom; Golding, William, 1911-1993 (Diamond Video, 1980)
When a group of schoolboys are stranded on a desert island, they turn into savages. A study in greed, power, and the innate animalistic/survivalistic instincts of human nature.